2015
DOI: 10.1111/ajt.13406
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Apoptosis Induces TGF-β Signaling-Dependent Host Endothelial–Mesenchymal Transition to Promote Transplant Arteriosclerosis

Abstract: Endothelial cells (ECs) apoptosis is an initial event in transplant arteriosclerosis (TA), resulting in allograft function loss. To elucidate the precise mechanisms of ECs apoptosis leading to neointimal smooth muscle cells (SMCs) accumulation during TA. We induced apoptosis in cultured ECs by overexpressing p53 through lentivirus-mediated transfection. ECs apoptosis induced the production of transforming growth factor (TGF)-b1 in both apoptotic and neighboring viable cells, leading to increased TGF-b1 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 58 publications
(78 reference statements)
1
29
0
Order By: Relevance
“…TGF-β can activate Ras/Erk MAPK signaling and PI3K/Akt in the TGF-β/non-Smad pathway, which plays important roles in EndMT and EMT in a TGF-β-dependent manner [30][31][32]. The activated Erk can also induce the phosphorylation of Smad.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β can activate Ras/Erk MAPK signaling and PI3K/Akt in the TGF-β/non-Smad pathway, which plays important roles in EndMT and EMT in a TGF-β-dependent manner [30][31][32]. The activated Erk can also induce the phosphorylation of Smad.…”
Section: Discussionmentioning
confidence: 99%
“…EndMT is induced by TGF-β1 in HUVECs. TGF-β1 is a powerful factor for induction of EndMT, although the effect depends of the treatment time and dose in different models (17). Relative VE-cadherin and α-SMA expression levels were determined by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of EndMT and the mechanisms regulating cell phenotype adaption during vascular remodeling are poorly understood. Studies have reported that mouse and human endothelial cells are induced by transforming growth factor (TGF)-β1 to transform into SM-like cells in which the expression of α-smooth muscle actin (α-SMA) is upregulated (17,18). Under the synergistic action of TGF-β1 and the Wnt signaling pathway, EndMT may be induced.…”
Section: Eofaz Inhibits Endothelial-to-mesenchymal Transition Throughmentioning
confidence: 99%
“…RNA expression was analysed by RT‐PCR using iQ SYBR Green Supermix in an iCycler Real‐Time PCR Detection System (Bio‐Rad). The following primer sequences were used: PDE4A: sense 5′‐AACTTTCCGCAGACGCCTT‐3′, antisense 5′‐ TCTGAGCGGTACAGGAAGGA‐3′, TGF‐β1: sense 5′‐AACTACTGCTTCAGCTCCAC‐3′, antisense 5′‐AGGACCTTGCTGTACTGTGT‐3′ . Expression was normalized to that of β‐actin.…”
Section: Methodsmentioning
confidence: 99%
“…The following primer sequences were used: PDE4A: sense 5′-AACTTTCCGCAGACGCCTT-3′, antisense 5′-TCTGAGCGGTACAGGAAGGA-3′, TGF-β1: sense 5′-AACTACTGCTTCAGCTCCAC-3′, antisense 5′-AGGACCTTGCTG-TACTGTGT-3′. 23 Expression was normalized to that of β-actin.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%